The Hunger Games : Catching Fire - Sawhney, Mohanbir; Goodman, Pallavi (London : Kellogg School of Management, 2016)
After the successful release of the first Hunger Games film in 2012, the film's distributor, Lionsgate, was preparing to release the next movie in the series, Hunger Games: Catching Fire. Fan expectations had grown after the success of Hunger Games and Lionsgate faced the challenge of keeping moviegoers interested and engaged in another Hunger Games movie. In an era marked by the rising popularity of digital and social media, Lionsgate knew that attracting fans to a sequel meant pushing the boundaries of traditional marketing tactics.Digital brand storytelling is about using digital media in a holistic way to tell a brand story and build excitement for an audience. Brand storytelling seeks to make a connection with the audience by giving them an emotional experience that resonates with them. While Lionsgate was aware that traditional marketing would need to be blended with a digital campaign to bring in moviegoers, it also needed to strike a careful balance between the two and choose the appropriate platforms to tell a cohesive story. Should Lionsgate launch a brand storytelling campaign to appeal to fans? Lionsgate's comparatively small marketing team gathered to brainstorm about how to execute such a campaign and position the film for another big success.
Originally published in Sawhney, M., & Goodman, P. (2016). The Hunger Games: Catching Fire: Using Digital and Social Media for Brand Storytelling.5-415-750. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lions Gate Films; Hunger Games; Hunger Games (Motion picture); Motion pictures -- Marketing